To the bone: Comment on "I wanted a skeleton ... they brought a prince": A qualitative investigation of factors mediating the implementation of a Performance Based Incentive program in Malawi - Dennis Pérez; Patrick Van der Stuyft; Valéry Ridde; Pierre Lefèvre (Elsevier, 2019)
Recently, McMahon and colleagues set out to build on a widely-used fidelity framework, assessing the role of moderating factors during the implementation of performance-based financing programs in Malawi. Their attempt draws again the attention to the importance of approaching real word implementation issues from a theoretical perspective. It also highlights the importance of fidelity assessment within process evaluation of health programs. In this comment we argue that theoretical developments in the field of implementation science in global health would benefit from an accurate understanding of existing conceptual frameworks as well as from taking into account all contemporary contributions. Keywords: Implementation research, Implementation fidelity, Conceptual framework, Performance-based financing